Uporaba umetne inteligence in kibernetska varnost na letališčih - Rauch, Robert (Trajnost, 2025)
Technological improvements based on innovative technologies, such as artificial intelligence, which are sustainability-oriented, have great potential. In the context of long-term growth in air travel, constant cost pressures on airports, and the rapid advancement of innovative technologies, numerous opportunities are emerging. However, the use of such technologies at airports also raises concerns about information security and privacy, which must be addressed through appropriate legislation, regulation, ethical guidelines, and security protocols. Therefore, airports must not neglect cybersecurity, which is becoming an increasingly significant challenge. In this paper, we will analyze some of the best practices.
Keywords: kibernetska varnost; letališča; sodobne tehnologije; umetna inteligenca